Athlete Medical Services at the Marathon and Race Walking Events During Tokyo 2020 Olympics - Makoto Sugawara; Makoto Sugawara; Yoshiaki Manabe; Yoshiaki Manabe; Fumihiro Yamasawa; Fumihiro Yamasawa; Yuri Hosokawa (Frontiers Media S.A., 2022)
Epidemiological data from race walk and marathon events suggest that a high incidence rate of exertional heat illness is associated with high ambient temperature and relative humidity. The 2020 Summer Olympics in Tokyo was no exception, which led the organizing committee to relocate the race walk and marathon competitions to Sapporo, which was predicted to experience much milder heat. Nonetheless, during the Games, Sapporo recorded the highest daytime ambient temperature in the past 97 years, with consecutive days over 30°C from July 22nd to August 7th, 2021. Five events (men's and women's 20 km race walk, men's 50 km race walk, women's and men's marathon) were held in Sapporo from August 5th to August 8th, 2021. The percentage of athletes who did not finish (DNF) in each event was 8.8% in men's 20 km race walk, 20.3% in men's 50 km race walk, 8.6% in women's 20 km race walk, 17.1% in women's marathon and 28.3% in men's marathon. A total of fifty athletes were transferred to the athlete medical station: 28 athletes completed the race (i.e., collapsed after finish line), while 24 were DNF athletes transported from the course. Forty-eight (96%) of athletes who were admitted to the athlete medical station exhibited signs and symptoms of exertional heat illness. Two athletes diagnosed with exertional heat stroke and three athletes diagnosed with severe heat exhaustion (rectal body temperature >39.5°C with or without central nervous system disturbance) were cooled using whole-body cold water immersion at the heat deck located within the athlete medical station. All athletes who were cooled successfully recovered without any complications. These athletes required an average of 14 ± 9.4 min (range, 6-30 min) to cool their rectal temperature below 39°C. These results show the importance for event organizers to prepare strategies to keep athletes cool, such as an ample amount of ice and water to supply whole-body cold water immersion.